Efforts to improve mathematics learning outcomes using the Realistic Mathematics Education (RME) learning model assisted by student number card media Class IV SDN-1 New Kasongan - Endang Sri Estimurti; Yuni Sriwihartati (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Background: Mathematics is a universal science that underlies the development of modern technology, has an important role in various disciplines and advances human thinking. There are still many students who seem less motivated, The results of initial observations at SDN-I Kasongan Baru show that interest in learning is low and tends to do things that are beyond their obligations as students, both in the learning process in class and outside the classroom. So the researcher concluded the need to apply a realistic mathematics education learning model assisted by card media to improve student learning outcomes. Objectives: This study aims to: (1) Determine the Mathematics learning activities of students and teachers using the Realistic Mathematics Education (RME) learning model in grade IV SDN-1 Kasongan Baru, (2) find out the improvement of learning outcomes with the Realistic Mathematics Education (RME) learning model. Method: This study uses the type of PTK research with the Realistic Mathematics Education (RME) research model. This research was carried out in grade IV of SDN-1 Kasongan Baru in the even semester of the 2023 academic year with the subjects of the study being 21 grade IV students. Data collection is carried out by Observation and Test methods. Data analysis uses qualitative and quantitative. Results and Dıscussion: The results showed that: 1) teacher and student activity after the observation results in cycle I showed that the average activity score of teachers and students was in the range of scale 2.7 and 2.9 with a fairly good category while in cycle II the observation results of teachers and students increased in the range of 3.3 and 3.3 with good category, 2) there is an improvement in Mathematics learning outcomes after applying the Realistic Mathematics Education (RME) learning model in grade IV SDN-1 Kasongan Baru. Conclusion: The realistic Mathematics Education (RME) learning model assisted by number card media can improve the mathematics learning outcomes of grade IV students of SDN-I Kasongan Baru.